2022
DOI: 10.1371/journal.pgph.0000154
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting road safety compliance in a low- and middle-income country: An observational study from Lebanon

Abstract: Road traffic injury is a major public health problem in Lebanon. This study aims to assess compliance with safety measures including seatbelt and helmet use in adults and children, and the prevalence of distracted driving among road users across Lebanon different governorates. It further aims to investigate predictors of compliance with seatbelt and helmet use. A cross-sectional observational field study was conducted at multiple governorates in Lebanon. Data collected included information on vehicles, road us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Our finding is like other studies that found that pedestrian and motorcyclist injuries were the main cause of TI injuries and that could be due to poor quality of the road, lack of pedestrian walkways, and lack of road safety awareness in India [ 13 , 14 ]. Further, few have argued about the behavior of motorcyclists such as not wearing helmets, alcohol consumption, and not obeying traffic signals which are the major factors for motorcycle road injury [ 15 , 16 ]. Similarly, few have argued some risk factors such as overspeeding, overloading, wrong-side driving, commercial place, and faulty road design could be possible risk factor for road accidents in Indian states [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding is like other studies that found that pedestrian and motorcyclist injuries were the main cause of TI injuries and that could be due to poor quality of the road, lack of pedestrian walkways, and lack of road safety awareness in India [ 13 , 14 ]. Further, few have argued about the behavior of motorcyclists such as not wearing helmets, alcohol consumption, and not obeying traffic signals which are the major factors for motorcycle road injury [ 15 , 16 ]. Similarly, few have argued some risk factors such as overspeeding, overloading, wrong-side driving, commercial place, and faulty road design could be possible risk factor for road accidents in Indian states [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 shows that the total mortality (death) rate of TI was 17.1 [CI: [14][15][16][17][18][19]] in 1990 which got reduced slightly to 16.9 [CI: [13][14][15][16][17][18][19][20]] in 2019. It shows that there was a substantial reduction in mortality between 1990 and 2019 in the age group under 5 and 5-14 years.…”
Section: Deaths Of Transport Injury and Its Sub-causementioning
confidence: 99%
“…The few studies that have assessed the relationship between extreme environmental temperatures and road traffic crashes have been undertaken in high-income countries, and the generalizability of their findings to low- and middle-income countries (LMICs) is limited due to variations in road safety regulations and compliance to them, climate adaptation policies, the quality of traffic infrastructure, and the age of the vehicle fleet, among other factors (Al-Hajj et al 2022 ; Ameratunga et al 2006 ; Heydari et al 2019 ; Plummer and Boyle 2017 ). This limited generalizability is important given that much of the global burden of disease due to road traffic crashes including 90% of the world’s road traffic-related deaths takes place in LMICs (Naeem 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…To visualize these dynamics, Fig. (7) presents boxplots illustrating the distribution of speeds for each cluster within various road scenarios. Cluster 1 drivers exhibit nuanced responses to road conditions.…”
Section: An Analysis Of Specific Driving Environment Characteristicsmentioning
confidence: 99%
“…Given these challenges, the complexity of the traffic safety environment in Lebanon appears to be multifaceted. It encompasses not only deteriorating infrastructure and lax enforcement of traffic laws but also poor driver awareness and training [5,6,7]. The situation is further aggravated by the rapid increase in the number of vehicles, which exceeds the capacity of existing infrastructure.…”
Section: Introduction 1context and Backgroundmentioning
confidence: 99%